2009
DOI: 10.1016/j.jneb.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Adherence to 5 Servings of Fruits and Vegetables per Day: A Theory of Planned Behavior Perspective

Abstract: The TPB may be a useful framework on which to base a 5-A-Day intervention for male and female college students of different ethnic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
73
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 23 publications
13
73
1
4
Order By: Relevance
“…The finding that affective attitude was more predictive than instrumental attitude was consistent with various studies, which found that the first was more effective in predicting various health behaviours (e.g., Conner, Godin, Sheeran, & Germain, 2013;Conner et al, 2015), and with evidence that meat consumption is related more strongly with affective attitude than a cognitive attitude (Aikman, Crites, & Fabrigar, 2006;Berndsen & Van der Pligt, 2004). The finding that subjective norm was not a significant predictor of intention is in accordance with previous studies, which found that subjective norm has a low or nonsignificant relationship to healthy eating (Blanchard et al, 2009;Louis, Chan, & Greenbaum, 2009) and particularly to a vegetarian diet (Povey et al, 2001), to the intention of substituting meat with a more plant-based diet (Graça, et al, 2015) or of reducing meat consumption (Zur & Klöckner, 2014;Zur, 2012). Importantly, the present study found that past behaviour was not a significant predictor of intention, responding to the issue noted by Richetin et al (2011) about the likely useful addition of past behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that affective attitude was more predictive than instrumental attitude was consistent with various studies, which found that the first was more effective in predicting various health behaviours (e.g., Conner, Godin, Sheeran, & Germain, 2013;Conner et al, 2015), and with evidence that meat consumption is related more strongly with affective attitude than a cognitive attitude (Aikman, Crites, & Fabrigar, 2006;Berndsen & Van der Pligt, 2004). The finding that subjective norm was not a significant predictor of intention is in accordance with previous studies, which found that subjective norm has a low or nonsignificant relationship to healthy eating (Blanchard et al, 2009;Louis, Chan, & Greenbaum, 2009) and particularly to a vegetarian diet (Povey et al, 2001), to the intention of substituting meat with a more plant-based diet (Graça, et al, 2015) or of reducing meat consumption (Zur & Klöckner, 2014;Zur, 2012). Importantly, the present study found that past behaviour was not a significant predictor of intention, responding to the issue noted by Richetin et al (2011) about the likely useful addition of past behaviour.…”
Section: Discussionsupporting
confidence: 91%
“…Multiple studies have applied this theory to a widespread assortment of health perspectives, including food and beverage consumption behaviors. [18][19][20][21][22][23] Even though there exists various definitions and measures of food and beverage consumption, as mentioned in these studies, there also exists an unadulterated idea that TPB is an excellent predicator of a range of measures of food and beverage consumption behavior for various populaces. TPB dictates that individuals have a higher chance to perform a specific health behavior if three requirements are met: they trust that the new behavior will lead to particular outcomes that they value, if they think that individuals whose opinions they value think they should implement the behavior, and if they believe that they have the necessary means and chances to accomplish the behavior.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…For example, behavioral beliefs related to the health benefits of healthful eating were associated with eating behavior in some samples 14,16 whereas behavioral beliefs related to the energizing effects of healthful eating were associated with eating behavior in another sample. 13 Control beliefs related to money, stress, and time were associated with FVC in one sample 16 whereas control beliefs related to access and preference were related to FVC in another. 13 It seems that specific belief-behavior relationships vary between contexts.…”
Section: Introductionmentioning
confidence: 97%
“…13 Control beliefs related to money, stress, and time were associated with FVC in one sample 16 whereas control beliefs related to access and preference were related to FVC in another. 13 It seems that specific belief-behavior relationships vary between contexts. Because TPB interventions must target and change underlying accessible beliefs to ultimately change behavior, 9 there is a need for further examination of beliefs and their association with eating behavior.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation